Homage to home: an architectural investigation at Stora Stenbrottet in the Kinnekulle region - Donnerhack, Ulrike (My University, 2022)
“Architecture is the very mirror of life. You only have to cast your eyes on buildings to feel the presence of the past, the spirit of a place; they are the reflection of society." - I. M. Pei - In this thesis, I return to my home region on Kinnekulle in order to explore how the design of a public building can connect to and enhance the experience of a place and the cultural history of a region. Through a research by design approach the thesis aims to investigate traditional stone- and timber building techniques from the area of Kinnekulle and explore how they could be translated into the typology of a modern visitors center and through this contribute to the knowledge on using stone and timber as a building material in an architectural project. The thesis engages with theory on architectural regionalism, tectonics and materiality and through studies on site, in models, sketches and drawings results in a two-part visitor center at the large quarry on Kinnekulle. One part tells the narrative of stone — its durability, strength and timelessness. The other part tells the tale of wood — its lightness and warmth. Through this the thesis aims to pay homage to two contrasting materials — to a place — and to the cultural heritage of Kinnekulle.